SYNERGY BETWEEN PANCASILA AND ISLAM IN THE REPUBLIC OF INDONESIA - Asyathun Azizah; Syamzaimar (PT Rahis Cendekia Indonesia, 2026)
Pancasila, as the foundation of the state and the ideology of the Indonesian nation, has values ​​that align with the teachings of Islam. This study aims to examine the synergy between Pancasila and Islam within the framework of the Unitary State of the Republic of Indonesia. The method used is a literature study with a normative and philosophical approach to the verses of the Qur'an, Hadith, and national documents. The results of the study indicate that each principle in Pancasila has a substantive alignment with Islamic principles. The first principle reflects the value of monotheism, the second principle is in accordance with the teachings of justice and humanity, the third principle is in line with the command of unity of the people, the fourth principle represents deliberation or shura, and the fifth principle reflects social justice and takaful ijtimai. This synergy proves that Pancasila does not conflict with Islam, but rather serves as a forum that accommodates religious values ​​in the life of the nation and state. The role of Islam as a majority has contributed significantly to the formation of national character, social ethics, and national spirit. Meanwhile, Pancasila functions as a unifying force for the diversity that exists in Indonesia. Thus, the integration of Pancasila and Islamic values ​​is key to maintaining the integrity of the Unitary State of the Republic of Indonesia. Implementing this synergy through education, policies, and social practices is expected to create a just, democratic, tolerant, and civilized society.